Constitutional Guarantee of Children's Human Rights Protection - Hadiarto Hadiarto; Muhammad Karyadie (Ridwan Institute, 2022)
The amendments made to the 1945 Constitution (UUD 1945) clearly provide protection for human rights. Children's rights are explicitly stipulated in Article 28B of the 1945 Constitution. This is a right of protection that must be guaranteed by the state in the state process. Although the 1945 Constitution as a result of the amendments has regulated the norms for the protection of children's rights, the 1945 Constitution has not fully accommodated the norms and principles of children's rights which are the spirit of the Convention on the Rights of the Child. Two of the 4 principles of the Convention on the Rights of the Child, namely: (i) the principle of the best interests of the child and (ii) the principle of respecting the views of the child has not been accommodated in the 1945 Constitution. Thus, the principle of the best interests of the child and the principle of respecting the views of the child have not yet become constitutional norms.